Study and analysis of discontinuity by using taper baluns - Aldahhan, Hussein; Qas Elias, Bashar (International Journal of Engineering and Technology, 2015)
A coplanar stripline (CPS) to microstrip line transition (MSL) are designed with high characteristics, such as wide band, low return loss and high insertion loss. Two types of tapers are proposed, exponential and triangular to decreases of discontinuity in the power flow in transmission line. The suggested design achieved reflection coefficient under -10 dB over wide band from 1 GHz to 3 GHz and insertion losses of less than 1 dB.